Surgical activity organization during COVID-19 outbreak: a teaching hospital experience - Bellini, Valentina; Cozzani, Federico; Del Rio, Paolo; Bignami, Elena Giovanna (Acta Biomedica Atenei Parmensis, 2020)
In order to continue the oncological surgical activity and the surgical emergencies, we have elaborated a reorganization of the surgical department. In particular, differentiated pathways for COVID-19 and NON-COVID-19 patients were promptly planned. This arrangement has involved structural and organizational changes almost daily, with great efforts of the health personnel, but allowing our hospital to be the only one in the area still able to guarantee patients safe access to surgical treatment.